2022
DOI: 10.3389/fchem.2022.951951
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing and screening ionic liquids and deep eutectic solvents for effective CO2 capture

Abstract: CO2 capture is essential for both mitigating CO2 emissions and purifying/conditioning gases for fuel and chemical production. To further improve the process performance with low environmental impacts, different strategies have been proposed, where developing liquid green absorbent for capturing CO2 is one of the effective options. Ionic liquids (IL)/deep eutectic solvents (DES) have recently emerged as green absorbents with unique properties, especially DESs also benefit from facile synthesis, low toxicity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 154 publications
2
15
0
Order By: Relevance
“…Considering the CO 2 /CH 4 selectivity, it was clarified that mixtures including ionic species (choline acetate, betaine hydrochloride, and choline chloride; ChCl) would be more effective than those composed of non-ionic species (Figure b). These data are consistent with the experimental results. Practically, a small amount of water is often added to reduce the viscosity of DESs; however, the effect of water addition on CO 2 absorption capacity is not clear. ,, Among the narrowed 17,681 mixtures, 438 were predicted to maintain satisfactory CO 2 absorption capacities even under humid conditions (Figure c). Further analyzing the role of ionic species, it was found that more effective absorbents would be obtained when ionic species act as an HBD (blue in Figure c).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Considering the CO 2 /CH 4 selectivity, it was clarified that mixtures including ionic species (choline acetate, betaine hydrochloride, and choline chloride; ChCl) would be more effective than those composed of non-ionic species (Figure b). These data are consistent with the experimental results. Practically, a small amount of water is often added to reduce the viscosity of DESs; however, the effect of water addition on CO 2 absorption capacity is not clear. ,, Among the narrowed 17,681 mixtures, 438 were predicted to maintain satisfactory CO 2 absorption capacities even under humid conditions (Figure c). Further analyzing the role of ionic species, it was found that more effective absorbents would be obtained when ionic species act as an HBD (blue in Figure c).…”
Section: Resultssupporting
confidence: 85%
“…They are obtained as mixtures of hydrogen-bonding donors and acceptors (HBDs and HBAs), are suitable for reducing production costs, and impose fewer adverse environmental effects. Exploring the physicochemical properties of DESs corresponds with green chemistry and engineering objectives. However, controlling physicochemical properties is less straightforward in DESs than in ILs, as it is impossible to predict the role of molecules (i.e., whether the molecule works as an HBA or HBD) in hydrogen-bonded mixtures solely from their chemical structures.…”
Section: Introductionmentioning
confidence: 99%
“…Here we could see that ionic ChCl-based 48 mixtures listed in Table 1 have higher CO2/CH4 selectivity than non-ionic mixtures, as in the previous reports. [19][20][21] The hydrogen-bonding capacity for ChCl was θChCl = tan -1 (0.0985/3.8047) = 1.4830°, which indicates that ChCl has strong HBA capacities, as reported previously. Additionally, θChCl > 0 indicates that ChCl exhibits weak HBD capacities.…”
Section: Screening By Cosmo-rssupporting
confidence: 82%
“…Notably, exploring the physicochemical properties of DESs corresponds with green chemistry and engineering objectives. [19][20][21][22] However, DES design is not straightforward because it is impossible to determine which of the vast arrays of hydrogen-bonded organic molecules will act as the HBD or HBA based solely on the chemical structure. Thus, the microscopic solution chemistry governing their macroscopic properties is unclear when organic molecules with both HBD and HBA groups are mixed.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al demonstrated that 1-methylimidazole is a phase separator that induces phase separation and an absorption promoter that increases the absorption rate [37]. Moreover, imidazole ionic liquids show good CO 2 absorption capacity [38]. Cheng et al studied the CO 2 absorption mechanism by deep eutectic solvents based on ethylene glycol and protic ionic liquid ([MEAH][Im]), formed by monoethanolamine with imidazole [39].…”
Section: Introductionmentioning
confidence: 99%